Opioids in the management of persistent non-cancer pain. Issue 11 (November 2016) - Thomson, Laura; Rait, Kiran; Miller, Lucy
Abstract: Persistent non-cancer pain (PNCP) is a chronic disabling condition with a high prevalence within Europe (20%) and associated economic burden. In recent years there has been a considerable increase in the prescription of long-term opioids for PNCP. However, many patients still report dissatisfaction with their treatment and the associated disability of PNCP remains high. Opioid related adverse effects, opioid misuse and associated morbidity and mortality remain an issue. This article reviews the evidence for the effectiveness of long-term opioids in the management of PNCP, the current guidelines and the associated adverse affects.